Towards ethical guidelines for fair data economy – thematic analysis of values of Europeans - Minna M. Rantanen (Germany, 2022)
Data has become a modern commodity and a resource that is produced,
shared and consumed in increasing amounts. This development has led to creation
of data economy ecosystems. These economies are complex socio-technical
systems, where the role of individuals as consumers and producers of data is vital.
Although recent events in existing data economies have raised awareness of value
of the personal data, there is very little research done about individuals and their
needs in these ecosystems.
In this paper individuals and their needs are researched in context of fair data
economy – an on-going project that aims to develop an ethical European data
economy that is fair to all of its actors. To create ethical governance guidelines,
values of European individuals are researched by means of thematic analysis
from 4,792 answers to two open question about fair data economy conducted in
Finland, France, Germany and the Netherlands. As a result, a value basis for the
governance model is formed.
Proceedings of the Third Seminar of Technology Ethics (Tethics 2019), Turku, Finland, October 23-24, 2019